2008
DOI: 10.1021/nl080277d
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hot-Plate Ignition Probability for Nanoparticle-Laden Diesel Fuel

Abstract: The present study attempts to improve the ignition properties of diesel fuel by investigating the influence of adding aluminum and aluminum oxide nanoparticles to diesel. As part of this study, droplet ignition experiments were carried out atop a heated hot plate. Different types of fuel mixtures were used; both particle size (15 and 50 nm) as well as the volume fraction (0%, 0.1%, and 0.5%) of nanoparticles added to diesel were varied. For each type of fuel mixture, several droplets were dropped on the hot pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
110
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(114 citation statements)
references
References 13 publications
3
110
0
1
Order By: Relevance
“…As for instance, recent experimental results have shown an anomalous thermal conductivity enhancement by introducing very small amounts of copper nanoparticles, carbon nanotubes, magnetite nanoparticles, among other colloidal particles in the liquid carriers. [1][2][3][4][5][6][7] In addition, enhanced ignition properties has been found on fuels containing aluminum nanoparticles. 5 Besides better heat transfer properties nanoparticles also act as catalysts and can help on the reduction in pollutant production.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As for instance, recent experimental results have shown an anomalous thermal conductivity enhancement by introducing very small amounts of copper nanoparticles, carbon nanotubes, magnetite nanoparticles, among other colloidal particles in the liquid carriers. [1][2][3][4][5][6][7] In addition, enhanced ignition properties has been found on fuels containing aluminum nanoparticles. 5 Besides better heat transfer properties nanoparticles also act as catalysts and can help on the reduction in pollutant production.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In addition, enhanced ignition properties has been found on fuels containing aluminum nanoparticles. 5 Besides better heat transfer properties nanoparticles also act as catalysts and can help on the reduction in pollutant production. 6 Basically, nanofluids are promising systems to enhance the efficiency of ignition and combustion of liquid fuels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jackson et al [10] revealed that addition of aluminum nanoparticles could substantially decrease the ignition delay time of slurries of n-dodecane. Tyagi et al [11] by using a simple hot-plate experiment, found that nano-aluminum significantly enhance the ignition probability of diesel fuel. Beloni et al [12] studied effects of pure aluminum, mechanically alloyed Al 0.7 Li 0.3 , and nanocomposite 2B + Ti as nano additives on flame length, flame speed and flame temperature of decane-based slurries.…”
Section: Introductionmentioning
confidence: 99%